Evaluasi Pelaksanaan Pembelajaran SMA Negeri 12 Padang - Siti Jamila; Nita Putri Utami (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to describe the form and implementation of mathematics learning evaluation applied by teachers at SMA Negeri 12 Padang which is used in grades X and XI (Independent Curriculum). The method used is a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation, compiled collaboratively through the KKG forum and have been adjusted to the academic calendar of the Ministry of Religion. The results of the study indicate that mathematics teachers in grades X and XI consistently apply diagnostic assessments (especially cognitive), formative assessments, summative assessments, affective evaluations, and cognitive. Based on the results of observations, the teaching tools achieved a success percentage of 96.67% in grades X and XI. This evaluation is adjusted to the characteristics of students at each level and is carried out through various strategies, ranging from providing trigger questions to participant observation and conceptual understanding. Follow-up such as remedial and enrichment are also provided according to student needs. The evaluation carried out has reflected the principle of holistic assessment by considering cognitive, affective aspects, and the achievement of learning objectives.